2013
DOI: 10.1111/1759-7714.12020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spider venom on inhibition proliferation of TE13 cells in vivo and in vitro

Abstract: Background: The aim of this study was to evaluate the cytotoxic and antitumor activity of spider venom (SV). Methods: Cell proliferation and cytotoxicity were determined by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…As presented in a previous study, flow cytometric analysis of TE13 and HeLa cells treated with crude M. raveni spider venom revealed that the main mode of cell death was necrosis, with minimal apoptotic cells. The researchers eventually concluded that apoptosis, necrosis, and cell lysis of tumors are the possible mechanisms by which the crude venom of M. raveni inhibited tumor growth [20]. It is therefore important to identify the responsible spider venom component and to determine the proper concentration in order to elicit the desired mode of cancer cell death.…”
Section: Discussionmentioning
confidence: 99%
“…As presented in a previous study, flow cytometric analysis of TE13 and HeLa cells treated with crude M. raveni spider venom revealed that the main mode of cell death was necrosis, with minimal apoptotic cells. The researchers eventually concluded that apoptosis, necrosis, and cell lysis of tumors are the possible mechanisms by which the crude venom of M. raveni inhibited tumor growth [20]. It is therefore important to identify the responsible spider venom component and to determine the proper concentration in order to elicit the desired mode of cancer cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo testing revealed that the tumor size was significantly decreased after 21 days of treatment with the venom. 32 2.1.2. Peptides targeting cancer cells.…”
Section: Spider Venoms In Biomedicinementioning
confidence: 99%